2003
DOI: 10.1242/jcs.00214
|View full text |Cite
|
Sign up to set email alerts
|

Secretory ribonucleases are internalized by a dynamin-independent endocytic pathway

Abstract: A), a nontoxic homolog. Microscopy studies indicate that both ribonucleases readily bind to the cell surface and are internalized via acidic vesicles. Blocking dynamindependent endocytosis prevents transferrin internalization but does not hinder RNase A internalization. ONC and G88R RNase A, which is a toxic variant, demonstrate enhanced cytotoxicity in the absence of clathrin-and dynamin-mediated endocytosis. The cytosolic entry of ribonucleases does not require an acidic environment or transport to the ER an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
134
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(136 citation statements)
references
References 72 publications
1
134
1
Order By: Relevance
“…RNase A is a cationic protein that is internalized by mammalian cells via endocytosis (49). This internalization is critical to the action of cytotoxic RNase A variants and homologs (50).…”
Section: Bioconjugationmentioning
confidence: 99%
“…RNase A is a cationic protein that is internalized by mammalian cells via endocytosis (49). This internalization is critical to the action of cytotoxic RNase A variants and homologs (50).…”
Section: Bioconjugationmentioning
confidence: 99%
“…By virtue of their basic pI values, RNases of the RNase A superfamily bind to the negatively charged surface of cells (23). As cells should be anxious to prevent foreign RNases from entering the cell, no RNase receptor is expected to be found but RNases enter cells by endocytosis (23).…”
Section: Contradictions In the Reason For The Cytotoxicity Of Rnases-mentioning
confidence: 99%
“…As cells should be anxious to prevent foreign RNases from entering the cell, no RNase receptor is expected to be found but RNases enter cells by endocytosis (23). To exert their cytotoxicity, the RNases have to be released from the endosomes into the cytosol.…”
Section: Contradictions In the Reason For The Cytotoxicity Of Rnases-mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the selectivity of the action of RNAses on cells cannot be mediated only by their electrostatic properties 14 . In the work 15 , it was shown that the internalization of certain cytotoxic RNAses occurs via clathrin-and dynaminindependent endocytosis, after which they were translocated through the membrane of endosomes and enter to the cytosol, where the realization of their cytotoxicity is occurred. In the process of translocation through the membrane, the protein is forced to interact with a hydrophobic region of a lipid bilayer.…”
mentioning
confidence: 99%